Multi-polydioxanone (PDO) scaffold for forehead wrinkle correction: A pilot study. (2nd October 2016) - Ko, Hyun Ju; Choi, Joon Yong; Moon, Hyoung Jin; Lee, Jin Woo; Jang, Sue Im; Bae, Il-Hong; Choi, Jin Kyu; Kim, Hyuk; Park, Won-Seok; Oh, Won Jong; Choi, Sun Young; Kim, Beom Joon
Abstract : Background: Forehead wrinkles are the result of contracture of the frontalis muscle and the skin aging process. Currently, hyaluronic acid filler and botulinum toxin are the main materials used for correction of these wrinkles. In addition, polydioxanone (PDO) thread has also been applied for this treatment.Objective: In order to evaluate the efficacy and safety of multi-PDO scaffold in animal and human skin, we tested PDO insertion in rat and mini-pig models and human volunteers with forehead wrinkles.Methods: A stent-shaped multi-PDO scaffold was inserted under the panniculus carnosus of rat dorsal skin and the subcutaneous layer of mini-pig dorsal skin and forehead wrinkles in three human volunteers.Results: Histological analysis at 12 weeks revealed evidence of de novo collagen synthesis, which was consistent with clinical results on photo evaluation.Conclusion: Stent-shaped multi-PDO scaffolds may be another effective and safe treatment modality for reduction of forehead wrinkles.